Phytoplankton composition, abundance, and diversity in the outer San Pedro Bay, Leyte, Philippines during August 2013-February 2014 - Corado, Retsie B.; Yap-Dejeto, Leni G. (2014)
A study on the composition, abundance, and diversity of phytoplankton in the outer portion of San Pedro Bay on August 2013 to February 2014 was done. Samples were collected every other month from waters near Marabut, Jinamoc, Palo, and Tanauan. Collection of water samples was done using a plankton net and WILDCO water sampler. Collected samples were fixed with 10 mL formalin. A total of 54 phytoplankton species, 35 diatoms, 17 dinoflagellates, chlorophyte, and cyanobacteria species were observed during the four month sampling period. Dominance of phytoplankton composition was observed in this order: Bacillariophyta> Chrysophyta> Chlorophyta> Cyanophyta. Marabut and Jinamoc, had comparable phytoplankton composition while Palo and Tanauan had more similar phytoplankton assemblage. August recorded the highest mean total cell density (280,000 cells/L) in Marabut and Chaetoceros sp. (57,000 cells/L) in Palo were dominant. Leptocylindrus sp. was abundant in October. Chaetoceros sp. was also abundant in December together with Skeletonema sp. October registered the lowest (26,000 cells/L) mean total cell density. Based on Shannon-Wiener index, August had the lowest diversity (1.9) while December and February had the highest diversity index (2.7). Harmful algal species were also found including: Cochlodinium sp., Dinophysis sp., Gonyaulax sp., Gymnodinium sp., Gyrodinium sp., Noctiluca sp., Prorocentrum sp., Peridinium sp., and Protoperidinium sp.
Undergraduate thesis (B.S. in Biology)--University of the Philippines, Tacloban.
Keywords: Phytoplankton -- composition -- Outer San Pedro Bay, Leyte, Philippines; Phytoplankton -- Abundance -- Outer San Pedro Bay, Leyte, Philippines; Phytoplankton -- Diversity -- Outer San Pedro Bay, Leyte, Philippines; Science and Technology